The Spirit of Belonging: Redemption, Reconciliation, and Responsibility in Jennings’ Acts Commentary - Waddell, Robby; Green, Chris E. W. (2025)
This article examines the theological vision for a Spirit-formed community cast in Willie James Jennings’ commentary on the Acts of the Apostles. Jennings highlights the ways in which the Spirit disrupts conventional boundaries of belonging, rejecting colonial constructs of identity that divide and alienate. By reinterpreting the communal life described in Acts, Jennings presents a counter-cultural, Spirit-led model of belonging that opposes coercion and segregation, advocating instead for intimate and transformative solidarity. Through analysis of key narratives like Philip and the Ethiopian eunuch and Peter’s vision at Cornelius’s house, Jennings argues that the Spirit continually draws the faithful into unexpected relationships, reorienting them toward an inclusive, just, and ever-expanding community. This Spirit-formed community, Jennings suggests, is marked by humility, justice, and the dynamic tension of ‘unfinished Pentecost’, a communal project that forever presses toward the fullness of reconciliation and shared humanity. The article explores Jennings’ insights into how this ongoing project of belonging remains an urgent invitation to rethink power, authority, and community in the Christian life today.
Keywords: Justice; Colonialism; Belonging; Luke-Acts; Willie James Jennings